AB0981 VALIDATION OF THE CAREGIVERS QUESTIONNAIRE (IMPACT OF PEDIATRIC RHEUMATIC DISEASES ON CAREGIVERS MULTIASSESSMENT QUESTIONNAIRE) IN PEDIATRIC RHEUMATIC DISEASES. (13th June 2020) - Fortuna, B.; García-Rodríguez, F.; Rubio, N.; Villlarreal, A. V.; Faugier, E.; Reyes, G.; Mendieta, S.; Peláez-Ballestas, I.; Jimenez, S.; Rosiles, S.; Guadarrama, J.
Abstract : Background: The CAREGIVERS questionnaire is used as a multidimension screening instrument for burden of caregivers, it allows to examine the impact of juvenile idiopathic arthritis (JIA) on several areas of the caregiver's life, looking for specific concerns and needs in which treatment could be required. This instrument has shown a good understanding among participants, reliability and consistency to measure the psychosocial and economic impact on primary caregivers of patients with JIA. Objectives: The aim of this study is to validate CAREGIVERS questionnaire with the most common pediatric rheumatic diseases, such as JIA, systemic lupus erythematosus (SLE) and juvenile dermatomyositis (JDM). Methods: The external validation phase of the constructed questionnaire will be carried out following Feinstein's clinimetric and psychometrics methodology, to measure the impact of the disease on the caregiver and create a risk profile for treatment detachment. Results: A total of 200 questionnaires are applied to caregivers of pediatric patients with rheumatic diseases: 109 caregivers of patients with JIA, 28 caregivers of patients with DMJ and 63 caregivers of patients with SLE. When analyzing all the questions together, a general Cronbach's alpha of 0.6751 was obtained (Table 1 ). Conclusion: The CAREGIVERS questionnaire showed to be validated to assess the impact of pediatric rheumatic diseases. References: [1]Keppeke, L.d., Molina, J., Miotto e Silva, V.B. et al. Psychological characteristics of caregivers of pediatric patients with chronic rheumatic disease in relation to treatment adherence. Pediatr Rheumatol 16, 63 (2018). https://doi.org/10.1186/s12969-018-0280-7 [2]Cohen EM, Morley-Fletcher A, Mehta DH, Lee YC. A systematic review of psychosocial therapies for children with rheumatic diseases. Pediatr Rheumatol [Internet]. Pediatric Rheumatology; 2017;15(1):6. Available from: http://ped-rheum.biomedcentral.com/articles/10.1186/s12969-016-0133-1 . [3]Torres-Made, M.D., Peláez-Ballestas, I., García-Rodríguez, F. et al. Development and validation of the CAREGIVERS questionnaire: multi-assessing the impact of juvenile idiopathic arthritis on caregivers. Pediatr Rheumatol 18, 3 (2020). https://doi.org/10.1186/s12969-020-0400-z [4]Feinstein AR. Clinimetrics. New Haven: Yale University Press, 1987. Disclosure of Interests: None declared